2022
DOI: 10.1111/add.15949
|View full text |Cite
|
Sign up to set email alerts
|

Characterising the use of varenicline: an analysis of the Australian dispensing claims data

Abstract: Background and aims: In Australia, patterns of use of smoking cessation medications and factors associated with their dispensing are currently not known. This study aimed to measure the demographic and clinical factors associated with varenicline dispensing compared with nicotine replacement therapy (NRT) and bupropion among first-time users of Pharmaceutical Benefits Scheme (PBS) subsidised smoking cessation medicines in Australia and to characterise those who discontinued varenicline treatment prematurely. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…Adherence to varenicline is known to be poor in the general population; most (60.4%) of those who are dispensed varenicline discontinue treatment after the initiation pack, and less than 5% of those dispensed varenicline complete 12 weeks of treatment. 26 Given the pragmatic nature of the study, the adherence rates observed in our study are on par with routine clinical practice.…”
Section: Discussionmentioning
confidence: 94%
“…Adherence to varenicline is known to be poor in the general population; most (60.4%) of those who are dispensed varenicline discontinue treatment after the initiation pack, and less than 5% of those dispensed varenicline complete 12 weeks of treatment. 26 Given the pragmatic nature of the study, the adherence rates observed in our study are on par with routine clinical practice.…”
Section: Discussionmentioning
confidence: 94%